Effect of hygrothermal aging on the mechanical properties of IMA/M21E aircraft-grade CFRP composite. (22nd May 2020) - Shetty, Kishora; Bojja, Ramesh; Srihari, Shylaja
Unidirectional carbon fiber-reinforced plastic (CFRP) IMA/M21E polymer composite was manufactured by standard autoclave curing method. This is a new aircraft-grade CFRP composite presently used in the manufacture of aircraft wing parts. Test specimens as per ASTM standards for weight gain, tensile and compression tests were obtained from this composite laminates. Some of the test specimens were subjected to hygrothermal (hot–wet) aging in an environmental chamber under three different conditions, that is, (i) 45°C/85% relative humidity (RH), (ii) 70°C/85% RH and (iii) 55°C/100% RH until reaching moisture absorption saturation. Matrix-dominated mechanical properties, that is, transverse tensile and longitudinal compression were determined for dry and hygrothermally aged test specimens. During mechanical testing in a servo-hydraulic test machine, the respective hygrothermal conditions were maintained while testing. It was noted that the rate of moisture absorption increases progressively and reaches saturation around 0.76–1.24 wt% depending on the aging conditions. Moisture absorption followed Fickian diffusion behavior in all the conditions of the study. Also, a software program was developed to predict the moisture content and time of saturation. The predicted results from this software program correlated with experimental results. It was observed that the presence of moisture reduced the tensile strength significantly by about 9–31% and compression strength by about 2–8%. Microscopic observation of tested samples was carried out using scanning electron microscope to study the failure behavior.